2010
DOI: 10.1007/s11136-010-9609-5
|View full text |Cite
|
Sign up to set email alerts
|

Does mode of administration matter? Comparison of online and face-to-face administration of a time trade-off task

Abstract: This comparison demonstrates that variability arising from mode of administration needs to be considered in developing health state valuations. While electronic administration has considerable cost advantages, particular attention to the design of the task is required. This has wider implications, as all modes of administration may have mode-specific impacts on the distribution of valuation responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 19 publications
(20 reference statements)
4
73
0
Order By: Relevance
“…Using a computer to elicit values instead of face-to-face interviews also may impact the comparability of the values to previous studies [36]. A computer based TTO has been used in previous EQ-5D studies [29], but often at an interview where assistance is available and not via the web.…”
Section: Discussionmentioning
confidence: 99%
“…Using a computer to elicit values instead of face-to-face interviews also may impact the comparability of the values to previous studies [36]. A computer based TTO has been used in previous EQ-5D studies [29], but often at an interview where assistance is available and not via the web.…”
Section: Discussionmentioning
confidence: 99%
“…22 A comparison of the online and face-to-face delivery of TTO found that the responses differed by administration mode, with the online sample displaying more variation in response. 31 Tests of the person trade-off (PTO) valuation technique across online and CAPI administrations also found potential differences across modes. 32,33 Therefore, iterative health-state valuation tasks administered online may generate different results from face-to-face studies, but it is not clear whether the difference comes from the mode of administration or an interaction between the iterative task and the mode of administration.…”
Section: What Mode Of Administration?mentioning
confidence: 99%
“…After the task began, there was no interaction between the four respondents, and the trained interviewer was instructed to only assist with matters of interpretation of the question, and any technology issues. The reason for using this electronic approach relative to a straightforward online survey was that recent evidence has suggested that results generated using that latter approach may produce large numbers of health state valuations clustered around -1, 0, and 1 [24]. Each respondent was paid $60 for completion of the survey.…”
Section: Recruitment and Data Collectionmentioning
confidence: 99%